Cytokine profiles in children with acute intussusception in South Africa. (October 2021) - Bessey, Theresa K.; Parashar, Umesh D.; Tate, Jacqueline E.; Madhi, Shabir A.; Jiang, Baoming; Groome, Michelle J.; ,
Abstract: Serum specimens of children hospitalized with acute intussusception (IS; n = 407) were analyzed for various pro- and anti-inflammatory cytokines to identify host markers specifically for IS compared to other surgical conditions (n = 235) or acute gastroenteritis (AGE; n = 68) in a cross-sectional study design. We showed that children with IS had elevated levels of pro-inflammatory cytokines IFN-γ, TNF-α, MIP-1β, IL-1β, IL-2, IL-6, IL-7, IL-8, and IL-17 as well as anti-inflammatory cytokines IL-1RA, IL-4, IL-5, and IL-13 compared to those admitted with surgical conditions or AGE symptoms, indicating these cytokines as markers for IS. In addition, we showed an increase in C-reactive protein (CRP) levels in children with IS. This study is the first to show a broad cytokine profile and identify cytokine markers in children with IS.